Practice theory and international relations - Lechner, Silviya, 1974-; Frost, Mervyn (Cambridge : Cambridge University Press, 2018)
Are social practices actions, or institutional frameworks of interaction structured by common rules? How do social practices such as signing a cheque differ from international practices such as signing a peace treaty? Traversing the fields of international relations (IR) and philosophy, this book defends an institutionalist conception of practices as part of a general practice theory indebted to Oakeshott, Wittgenstein and Hegel. The proposed practice theory has two core aspects: practice internalism and normative descriptivism. In developing a philosophical analysis of social practices that has a special relevance for international relations, Silviya Lechner and Mervyn Frost depart from Pierre Bourdieu's sociology of practice that dominates the current'practice turn' in IR. The authors show that the contemporary global realm is constituted by two distinct macro practices - the practice of sovereign states and that of global rights.
Machine generated contents note: Introduction: Mapping out the Problem of Practices; Part I. A Philosophical Analysis of Social Practices: 1. Practice Theory: A Preliminary View; 2. Bourdieu and the Practice Turn in International Relations; 3. Practice Theory: A Basic Philosophical Template; Part II. Practices in International Relations: 4. Two Core Practices in International Relations: A Neo-Hegelian Perspective; 5. The Dialectic of Global Practices; 6. Practice Theory, Macro Practices and the Study of International Relations.
Title from publisher's bibliographic system (viewed on 30 Aug 2018).
Keywords: International relations -- Philosophy